PENGELOLAAN LABORATORIUM DI PERGURUAN TINGGI - Prasetya Sigit Santosa (Majalah Ilmiah Bahari Jogja, 2017)
Laboratory or workshop management as a process that directs the stepsof each workshop user to always comply with the rules or regulationsapplicable in the workshop. Management in order to realize the common goal ofthe workshop is always in a clean, tidy, maintained and maintained condition.Laboratory management as a strategy to achieve laboratory objectivesthrough planning, organizing, mobilizing, using and monitoring all laboratoryresources to achieve goals optimally. Laboratory resources include: instructors,tenants, facilities and infrastructure. Laboratory is a place of observation,experiment, practice and testing of concept and technology. Each user of theworkshop should know and pay attention to it during the use of the workshopor during the workshop. In order for it can be well conditioned it is necessaryto have a proper and clear workshop management. In order for the condition ofevery tool that is in the workshop is always awake, besides the enactment of aregulation then it should also be held maintenance maintenanceworkshop.Keywords: Laboratory, Workshop